The Hague Judgment: A victory with pain and without glory - Humala Aragón, Milagro Chino Née (2014)
The International Court of Justice is the principal judicial organ of the United Nations (UN). It has its seat in The Hague (The Netherlands). It was established by the Charter of the United Nations signed, in its Article 92, on June 26, 1945 in San Francisco to respond to the main objective of the UN to maintain international peace and security.